Структурнi змiни газового факела при настаннi пульсацiйного режиму горiння - Trofimenko, M. Yu.; Aslanov, S. K.; Smolyar, V. P. (Publishing house "Academperiodika", 2018)
An open household gas flame burning in the air atmosphere is studied. A concept of the stoichiometric ratio is clarified for such system on the basis of the observable closed inner cone formation and the pulsating combustion mode onset. We point out the higher combustion efficiency after the transition to a diluted mixture and the pulsating combustion. We also note that several different parameters may act as the limiting factors under certain oxidant–fuel ratios.